PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN DENGAN KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING - Nova Rizca Pratiwi (Jurnal Ekonomi Manajemen dan Bisnis, 2021)
Competition in business is become more competitive, so it’s required to innovate and provide the best products and services for winning the business competition. Zama Homewear is one of the MSMEs that produces embroidery nightgowns of Malang. Zama Homewear for winning the business competition is required to innovate in maintaining and improving customer satisfaction. This is because customer satisfaction is one of the keys to the continuity and progress of a business. The purpose of this study was to determine and analyze the direct effect of price and product quality on customer satisfaction and the indirect effect on customer satisfaction through purchasing decisions as an intervening variable. This type of research is descriptive quantitative research with a random questionnaire approach. The population in this study were all Zama Homewear customers as many as 4.799 people with a research sample of 98 respondents. The results show 1) there is a significant effect of price on purchasing decisions, 2) there is a significant effect of product quality on purchasing decisions, 3) there is a significant influence on purchasing decisions on customer satisfaction, 4) there is a significant effect of price on customer satisfaction, 5) there is a significant influence product quality on customer satisfaction, 6) there is a significant effect of price on customer satisfaction through purchasing decisions as an intervening variable, 7) there is a significant effect of product quality on customer satisfaction through purchasing decisions as an intervening variable.